Azide–Alkyne Interactions: A Crucial Attractive Force for Their Preorganization for Topochemical Cycloaddition Reaction. Issue 28 (1st April 2022) - Bhandary, Subhrajyoti; Pathigoolla, Atchutarao; Madhusudhanan, Mithun C.; Sureshan, Kana M.
Abstract: A new class of attractive intermolecular interaction between azide and ethynyl structural entities in a wide range of molecular crystals is reported. This interaction was systematically evaluated by using 11 geometrically different structural motifs that are preorganized to direct a solid‐state topochemical azide–alkyne cycloaddition (TAAC) reaction. The supramolecular features of the azide–alkyne interaction were mapped by various crystallographic and quantum chemical approaches. Topological analysis shows the noticeable participation of electron density in the azide⋅⋅⋅alkyne interactions. Interestingly, reorientation of the atomic polarizabilities in vicinal azide and alkyne groups upon interaction in crystals favors soft orbital‐guided TAAC reactions. Moreover, various solid‐state and gas‐phase energy decomposition methods of individual azide⋅⋅⋅alkyne interactions summarize that the strength (varies from −5.7 to −30.1 kJ mol −1 ) is primarily guided by the dispersion forces with a influencing contribution from the electrostatics. Abstract : A complete crystallographic, experimental and quantum‐chemical investigation for novel azide⋅⋅⋅alkyne supramolecular contacts in molecular crystals has established the directing role of such favorable interactions in topochemical cycloaddition reactions. The origin, geometry, and energetics of azide⋅⋅⋅alkyne contacts have been extensively probed through topological analysis, a reduced density gradient method, electrostatic potential maps, and solid‐state and gas‐phase energy decomposition analysis. This new attractive interaction may be used in designing functional crystalline materials.